Space Weapons Earth Wars - Preston, Robert (RAND Corporation, 2002)
This overview aims to inform the public discussion of space-based weapons by examining their characteristics, potential attributes, limitations, legality, and utility. The authors do not argue for or against space weapons, nor do they estimate the potential costs and performance of specific programs, but instead sort through the realities and myths surrounding space weapons in order to ensure that debates and discussions are based on fact.